The impact of neutral impurity concentration on charge drift mobility in n-type germanium. (3rd July 2017) - Mei, H.; Wang, G.-J.; Yang, G.; Mei, D.-M.
Abstract: The impact of neutral impurity scattering of electrons on the charge drift mobility in high purity n-type germanium crystals at 77 Kelvin is investigated. We calculated the contributions from ionized impurity scattering, lattice scattering, and neutral impurity scattering to the total charge drift mobility using theoretical models. The experimental data such as charge carrier concentration, mobility and resistivity are measured by Hall Effect system at 77 Kelvin. The neutral impurity concentration is derived from the Matthiessen's rule using the measured Hall mobility and ionized impurity concentration. The radial distribution of the neutral impurity concentration in the self-grown crystals is determined. Consequently, we demonstrated that neutral impurity scattering is a significant contribution to the charge drift mobility, which has a dependence on the concentration of neutral impurities in high purity n-type germanium crystal.